NICE's recent guidelines on "the size of your waist" unfairly penalizes shorter people. Issue 4 (July 2022) - Nevill, Alan M.; Duncan, Michael J.; Myers, Tony
Abstract: The National Institute for Clinical Excellence (NICE) has just released its latest guidelines to assess and predict health risk, such as type 2 diabetes, hypertension or cardiovascular disease. Their latest advice is "Keep the size of your waist to less than half of your height". We believe this advice is flawed and will seriously and unfairly penalize shorter people and lull taller people into a false sense of security. In this short communication, we provide this evidence. We consider this a serious oversight by NICE and feel strongly that this evidence needs to be made available in the public domain.